2014
DOI: 10.1002/hrm.21588
|View full text |Cite
|
Sign up to set email alerts
|

Enjoying New Ways to Work: An HRM‐Process Approach to Study Flow

Abstract: This article investigates the relationships between human resource management practices associated with New Ways to Work (employee empowerment, home‐based teleworking, and creating trust relationships) and work‐related flow as experienced by employees (absorption, work enjoyment, and intrinsic work motivation). Hypotheses, based on a combined perspective integrating insights from the HRM‐process model and the job demands‐resources model, are tested using multiactor multilevel data comprising employees (N = 1,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
149
0
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(172 citation statements)
references
References 78 publications
6
149
0
17
Order By: Relevance
“…On the basis of previous research within the Job Demands -Resources (JD-R) framework, we can conclude that the organizational context in the form of challenging job demands and resources, as well as absence of hindrance job demands plays an important role in facilitating flow (see Bakker 2005Bakker , 2008Demerouti 2006;Peters et al 2014;Van der Heijden and Bakker 2011). Structural job demands and resources as perceived by individual employees are under the influence of top-down processes that originate in human resource practices and leadership.…”
Section: Organizational Contextmentioning
confidence: 97%
See 1 more Smart Citation
“…On the basis of previous research within the Job Demands -Resources (JD-R) framework, we can conclude that the organizational context in the form of challenging job demands and resources, as well as absence of hindrance job demands plays an important role in facilitating flow (see Bakker 2005Bakker , 2008Demerouti 2006;Peters et al 2014;Van der Heijden and Bakker 2011). Structural job demands and resources as perceived by individual employees are under the influence of top-down processes that originate in human resource practices and leadership.…”
Section: Organizational Contextmentioning
confidence: 97%
“…The WOLF shows satisfactory factorial validity in a range of studies carried out in various cultures and using various languages. More specifically, the three-factor structure of the WOLF was confirmed in The Netherlands (Bakker 2008; Van der Heijden and Bakker 2011;Peters et al 2014), Norway (Hofslett Kopperud and Vivoll Straume 2009), Spain (Salanova et al 2006), Italy (Zito et al 2015), South Africa (Geyser et al 2015), and Pakistan (Zubair and Kamal 2015). One study carried out in Australia (Happell et al 2015) found that the items representing the work enjoyment and intrinsic motivation dimensions of the WOLF loaded on one dimension.…”
mentioning
confidence: 94%
“…Motivation is further related to the experience of enjoyment (Peters, Poutsma, Van der Heijden, Bakker, & de Bruijn, 2014) and to higher performance (Cerasoli, Nicklin, & Ford, 2014), which should both induce a more positive evaluation of one's work and consequently lead to increases in job satisfaction and person-job fit. In contrast to this gain mechanism, low levels of resources should lead to further loss of resources, because individuals with low resources are more vulnerable to stressful situations, which will place a strain on available resources (Hobfoll, 2002).…”
Section: Correlates and Outcomes Of Motivational Profilesmentioning
confidence: 99%
“…This has, in turn, set the trend for a new type of employee not only with a greater span of autonomy but also increased accountability (Allvin et al, 2011;Peters et al, 2009Peters et al, , 2014, often referred to as boundaryless work (Allvin et al, 2011(Allvin et al, , 2013 or 'New Working Conditions' (Peters et al, 2009). Moreover, the rapid development of boundary transcending information and communications technologies (ICT), teleworking, and flexworking systems has led to more flexible forms of work organization.…”
mentioning
confidence: 99%
“…This applies particularly to professionals who typically set their own work schedules and self-manage how they work in time and space (Allvin et al, 2013). As such, they can be said to have high time-spatial flexibility (Peters et al, 2009(Peters et al, , 2014. Consequently, these professionals need to manage the increasingly blurred boundaries between their work and personal lives and construct a well-functioning balance between the two.…”
mentioning
confidence: 99%